Analisis Konsep Manajemen Modal Kerja dan Pengaruhnya Terhadap Kinerja Keuangan Perusahaan - Tibrizi, Ahmad; Muzaki, Ikhwan; Sutopo, Agung Ramadhan; Falakh, Iqbal Fathul; Ramadani, Siti Padilah; Handayani, Julia; Jannah, Mukhlishotul (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the concept of working capital management and its effect on a company’s financial performance. Working capital management is an important aspect of short-term financial management, which is related to the management of current assets such as cash, receivables, and inventory. A common problem faced by companies is the imbalance between liquidity and profitability, which can affect overall financial performance. The research method used is a qualitative approach with a literature study design, by reviewing various sources such as scientific journals and relevant books published within the last five years. The data analysis technique is conducted descriptively by explaining the concept of working capital management and linking it to financial performance based on previous research findings. The results of the study indicate that working capital management has a significant effect on a company’s financial performance. Efficient management of working capital can increase profitability while maintaining liquidity. On the other hand, ineffective management can lead to an imbalance that negatively impacts the company’s financial condition. In addition, the efficiency of working capital management can also be assessed through the cash conversion cycle, where a shorter cycle indicates better financial performance. Therefore, it can be concluded that working capital management plays a strategic role in improving a company’s financial performance. Companies are expected to implement appropriate working capital management policies in order to achieve a balance between liquidity and profitability.